2023
DOI: 10.1002/masy.202100413
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stimulated Properties of Zinc Selenide Doped with Pr and (Ag,Pr) Phosphors

Abstract: The evaluation of trapping parameters activation energy, frequency factor, electron's life time in traps, capture cross-section, kinetics order, etc. are the most important studies in the field of themoluminescence. The thermoluminescence (TL) properties of Pr and (Ag, Pr) doped ZnSe phosphors are studied at three uniform heating rates between the temperature of 130K and 370K after excitation by UV radiation (365 nm). Trapping parameters of these phosphors have been determined and its nature is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It is found that the value of life time of electrons in traps increases with the increase in temperature. [2][3][4][5]16] It is evident that the value of the capture cross-section decreases with the increase of activation energy, this confirms the physical principle that the greater the trap depth lesser the capture probability. The kinetics analysis of glow curves was also carried out on the basis of symmetry factor (µ g ).…”
Section: Sl Nomentioning
confidence: 66%
See 4 more Smart Citations
“…It is found that the value of life time of electrons in traps increases with the increase in temperature. [2][3][4][5]16] It is evident that the value of the capture cross-section decreases with the increase of activation energy, this confirms the physical principle that the greater the trap depth lesser the capture probability. The kinetics analysis of glow curves was also carried out on the basis of symmetry factor (µ g ).…”
Section: Sl Nomentioning
confidence: 66%
“…For any order of kinetics, the trap depth can be fairly known with sufficient accuracy using the relation [2][3][4][5]12,13]…”
Section: Curie's Methodsmentioning
confidence: 99%
See 3 more Smart Citations